ROLE OF VITAMIN-D SUPPLEMENTATION IN COVID-19 PATIENTS - SALMAN, M; ZAMAN , S; AYMUN, U; KHAWAR , S; KHAN, I; KARIM, A (Biological and Clinical Sciences Research Journal, 2023)
COVID-19 has become a global pandemic and has affected millions of people worldwide. While there is still much to learn about the virus, it is clear that individuals with weakened immune systems and pre-existing health conditions are at higher risk of severe illness and death. The study’s main objective is to find the role of Vitamin-D supplementation in COVID-19 patients. The study included 300 COVID-19 patients admitted to a tertiary care hospital between January 2021 and May 2021. Using computer-generated randomization, participants were randomly assigned to either the intervention group or the control group. The intervention group received a daily dose of 4000 IU of Vitamin D3 for 14 days, while the control group received standard care without Vitamin D supplementation. Per hospital guidelines, all patients received standard medical treatment for COVID-19, including oxygen therapy, antiviral therapy, and corticosteroids. The study showed that Vitamin D supplementation significantly reduced the time to clinical improvement in COVID-19 patients. The median time to clinical improvement was 7 days in the intervention group, compared to 9 days in the control group (p <0.001). The intervention group also had a significantly shorter length of hospital stay, with a median of 9 days, compared to 11 days in the control group (p <0.001). In conclusion, vitamin D supplementation’s role in treating COVID-19 patients is an area of active research and has generated considerable interest in the scientific community. The results of the available studies suggest that vitamin D supplementation may have potential benefits in reducing the risk of severe COVID-19 and improving clinical outcomes.